Dari Mitos ke Metaverse: Digitalisasi Aset Ekologis-Spiritual Hutan Adat sebagai Model Ekonomi Konservasi Lintas Iman di Indonesia (Studi Kasus Komparatif: Sumatera Utara, Yogyakarta, Kalimantan, dan Bali) - Suheri Harahap; Zulkarnain Zulkarnain (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2026)
Customary forests in Indonesia serve not only ecological functions but also embody the spiritual values, cultural heritage, and collective identity of indigenous communities. In regions such as North Sumatra, Yogyakarta, Kalimantan, and Bali, these forests are regarded as sacred spaces preserved through myths, rituals, and time-honored customary rules. However, modernization, industrial expansion, and the lack of cultural digitization pose serious threats to their continued existence. This study aims to analyze the transformation of the ecological-spiritual values of customary forests into a digital-based conservation economy model, utilizing the metaverse and digital technologies. A qualitative research method was employed, involving a literature review and a comparative analysis of several indigenous territories in Indonesia. The findings indicate that digitizing cultural and ecological assets can serve as a modern conservation tool, bridging traditional values with the digital creative economy. The metaverse offers the potential to create a virtual space that sustainably represents customary forests, cultural rituals, environmental education, and interfaith spiritual tourism. Beyond strengthening local cultural identity, this approach creates new economic opportunities through digital ecotourism, cultural NFTs, and virtual educational platforms. The study underscores that integrating local traditions with digital technology can establish a future conservation model that is inclusive, sustainable, and adaptable to global developments.